Distal impact ejecta layers : a record of large impacts in sedimentary deposits - Glass, Billy P.; Simonson, Bruce M. (Heidelberg : Springer, 2013)
'Impact cratering is an important geological process on all solid planetary bodies, and, in the case of Earth, may have had major climatic and biological effects. Most terrestrial impact craters have been erased or modified beyond recognition. However, major impacts throw ejecta over large areas of the Earth's surface. Recognition of these impact ejecta layers can help fill in the gaps in the terrestrial cratering record and at the same time provide direct correlation between major impacts and other geological events, such as climatic changes and mass extinctions. This book provides the first summary of known distal impact ejecta layers.'--P. [4] of cover.
Introduction -- Impact crater formation, shock metamorphism, and distribution of impact ejecta -- Distal impact ejecta layers : recognition, confirmation, dating, and determining source craters -- Cenozoic microtektite/ejecta layers -- Mesozoic spherule/impact ejecta layers -- Paleozoic impact spherule/ejecta layers -- Proterozoic impact spherule/ejecta layers younger than 2.4 Ga -- Spherule layers near the Archean-Proterozoic boundary -- Paleoarchean spherule layers -- Modeling variations in distal impact ejecta/spherule layers through space and time -- Distal impact ejecta layers and earth history -- Appendix A : recovery of ejecta material from confirmed, probable, or possible distal ejecta layers.
Includes bibliographical references (p. 641-705) and index.
Keywords: Cryptoexplosion structures; Cratering; Sediments (Geology).; Geology, Stratigraphic